Conceptual and methodological signiﬁ-cance of Bacon’s theory of idols: modern projections - Liashchynskaya, Iryna I. (Journal of the Belarusian State University. Philosophy and Psychology, 2024)
The article is devoted to the analysis of Bacon’s theory of idols in the context of communicative practices of postmodern society. Modern projections of all types of idols of F. Bacon in the space of web communication are presented. The me thodological signiﬁcance of this theory for the analysis of various phenomena of modern media culture is revealed (fake, hype, trolling, ﬂaming, following, etc.). The essential and functional commonality of these phenomena and idols of knowledge, which were revealed by the English philosopher, has been established. The negative role of modern idols of knowledge for humans and society is analysed. The manipulative of character modern idols is explicated and ways to minimise their harmful effects are identiﬁed.